A Gigabit VLC receiver that incorporates a fluorescent antenna and a SiPM - Ali, W; Manousiadis, P; O'Brien, D; Turnbull, G; Samuel, I; Collins, S (IEEE, 2021)
In this paper we demonstrate a novel optical receiver for visible light communications that combines a fluorescent antenna and a silicon photomultiplier (SiPM). The fluorescent antenna is configured in a slab geometry to collect and absorb an incoming optical data signal, and to waveguide the resulting fluorescence to an edge where it is detected by the SiPM. The antenna incorporates the fluorophore, pentafluorene, selected for its very high bandwidth of 245 MHz, high photoluminescence quantum yield of 90%, and emission spectrum that matches the wavelengths most efficiently detected by the SiPM. The performance of a receiver, comprising the fluorescent antenna and a J-series 30020 SiPM manufactured by ON Semiconductor, was assessed in a 30 cm data link with a 405 nm GaN laser diode transmitter, both in the dark and under 500 lux of ambient white light. The fluorescent antenna successfully rejects ambient light by a factor of 20, limited by extrinsic scattering in the thin film. Using on-off-keying with decision feedback equalization, a maximum data rate of 1.4 Gbps was demonstrated in 500 lux of ambient light. Using the pentafluorene antenna plus a BG3 filter, provides a 200 fold suppression of ambient light, and can increase the data rate of the receiver at low signal powers by up to a factor of 2. When operating in ambient light the composite receiver requires only 2.5 times more signal power than when it operates in the dark, with this power penalty reducing to a factor of 1.2 at 1 Gbps.